In vitro and in vivo cytotoxicity assessment of glyphosate and imazethapyr-based herbicides and their association - Costa, Gessyca; Fernandes, Andréia; Santos, Thaís; Brito, Lara; Rodrigues, Laís; Valadares, Marize; Felzenszwalb, Israel; Ferraz, Elisa [UNESP]; Morais Leme, Daniela [UNESP]; Oliveira, Gisele [UNESP] (Taylor & Francis, 2022)
Resistance to glyphosate herbicide has initiated usage of combined application of herbicides as a weed control measure. Imazethapyr-based herbicides associated with glyphosate herbicide seem to be an alternative to suppress weed resistance. The aim of this study was to examine the adverse effects of Glyphosate Atanor 48® (ATN) and Imazethapyr Plus Nortox® (IMZT) formulations in both single forms and mixtures using HepG2 cells and zebrafish early-life stages models. Data demonstrated cytotoxicity due to exposure to ATN, IMZT for both models, as follows: (1) ATN (0.5 mg/L), IMZT (5 mg/L), and M3 (0.05 mg/L ATN + 5 mg/L IMZT) increased cytotoxicity by disturbing the mitochondrial activity of HepG2 cells 24 hr after exposure; (2) ATN and IMZT (5 mg/L), and M3 (0.05 mg/L ATN + 5 mg/L IMZT) also decreased the integrity of the membrane of HepG2 cells after 24 hr incubation; (3) only ATN and IMZT (5 mg/L) in their single forms diminished the mitochondrial potential of zebrafish; (4) ATN (single form) at 0.5 mg/L induced apoptosis in zebrafish larvae. In conclusion, these herbicides in their single forms appeared to produce greater cytotoxicity to HepG2 cells and zebrafish compared to the herbicide mixtures.
Keywords: cytotoxicity; Formulations; HepG2; mixtures; zebrafish